The effect of NF-κB signaling pathway regulation on PD-L1 expression of Enterococcus faecalis LTA-stimulated macrophages - YANG Yanling, LIU Runze, SUN Qing, FAN Wei (Editorial Office of Stomatology, 2024)
Objective To investigate the effect of Enterococcus faecalis (E. faecalis) lipoteichoic acid (LTA) on the expression of the macrophage immune checkpoint-programmed cell death protein ligand 1 (PD-L1) and explore the possible regulatory mechanisms. Methods In vitro model was established by stimulating mouse monocyte macrophage cell line (RAW264.7) with different concentrations of E. faecalis LTA. PD-L1 expression and nuclear factor kappa-B (NF-κB) p65 phosphorylation level were detected using flow cytometry, quantitative real-time polymerase chain reaction (qRT-PCR), Western blot and cellular immunofluorescence. Macrophages were pretreated with the NF-κB signaling pathway inhibitor BAY 11-7082, then the expression of PD-L1 and p65 phosphorylation level were detected by the above methods. Results LTA induced PD-L1 expression in RAW264.7 cells, and p65 phosphorylation level increased (P<0.05). Inhibition of the NF-κB signaling pathway could reduce p65 phosphorylation level, simultaneously reducing the expression of PD-L1 on LTA-stimulated RAW264.7 cells (P<0.05). Conclusion E. faecalis LTA can promote the PD-L1 expression of macrophages and this process is regulated by the NF-κB signaling pathway, which provides further insights into the occurrence and treatment of chronic periapical inflammation.